2017
DOI: 10.1007/s40477-017-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution ultrasonography and shear-wave sonoelastography of a cystic radial nerve Schwannoma

Abstract: Peripheral nerve tumors are often evaluated with magnetic resonance imaging (MRI), although there are many advantages offered with high-resolution ultrasonography (HRUS). This case report emphasizes the value of HRUS in the diagnosis and management of a patient with a cystic radial nerve Schwannoma. In addition, information on tumor stiffness, obtained with shear-wave sonoelastography (SWE), is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…This difference might be attributed to the relative proximity of the radial nerve at this site to the humerus. Battaglia et al 25 studied a single case of benign peripheral nerve schwannoma of the radial nerve and found that the elasticity ranged from 24 to 30 kPa by SWE, coinciding with its soft consistency and benign nature. The authors referred to the reference values of other musculoskeletal structures to indicate the benign nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be attributed to the relative proximity of the radial nerve at this site to the humerus. Battaglia et al 25 studied a single case of benign peripheral nerve schwannoma of the radial nerve and found that the elasticity ranged from 24 to 30 kPa by SWE, coinciding with its soft consistency and benign nature. The authors referred to the reference values of other musculoskeletal structures to indicate the benign nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Battaglia et al (26) described a case of cystic radial nerve schwannoma diagnosed using high-resolution ultrasonography, emphasizing the value of US in the diagnosis and management of the patient. The case listed “contiguity of the tumor with the nerve of origin” as one of the signs clearly observed on US.…”
Section: Discussionmentioning
confidence: 99%
“…Batagalia et al had reported a case of cystic degeneration of schwannoma of the deep branch of radial nerve. The sonographic features that enabled them to clinch the diagnosis were eccentric location, continuation with the nerve and stiffness of the lesion measured with shear wave sonoelastography [7].…”
Section: Discussionmentioning
confidence: 99%